Combination of PD-1 blockade and RetroNectin®-activated cytokine-induced killer in preheavily treated non-small-cell lung cancer: a retrospective study. (23rd October 2018) - Zhao, Lingdi; Han, Lu; Zhang, Yong; Li, Tiepeng; Yang, Yonghao; Li, Wei; Shang, Yiman; Lin, Hongwei; Gao, Quanli
Aim: To analyze the efficacy of PD-1 blockade combined with RetroNectin ® -activated cytokine-induced killer (R-CIK) cells in preheavily treated advanced non-small-cell lung cancer (NSCLC).Methods: We retrospectively analyzed patients with advanced NSCLC who received PD-1 blockade combined with R-CIK cells whose treatments failed at least two regimens.Results: The median number of previous treatment regimens was three (range: 2–7). Partial remission was achieved in two patients, stable disease in four patients and one patient experienced progressive disease. The median time-to-progression was 4.8 months.Conclusion: PD-1 blockade combined with R-CIK cells is safe and effective in patients with advanced NSCLC who have failed at least two treatment regimens.